Applying propensity scores estimated in a full cohort to adjust for confounding in subgroup analyses - Rassen, Jeremy A. (2011)
A correctly-specified propensity score (PS) estimated in a cohort (“cohort PS”) should in expectation remain valid in a subgroup population. We sought to determine whether using a cohort PS can be validly applied to subgroup analyses and thus add efficiency to studies with many subgroups or restricted data. In each of 3 cohort studies we estimated a cohort PS, defined 5 subgroups, and then estimated subgroup-specific PSs. We compared difference in treatment effect estimates for subgroup analyses adjusted by cohort PSs versus subgroup-specific PSs. Then, 10M times, we simulated a population with known characteristics of confounding, subgroup size, treatment interactions, and treatment effect, and again assessed difference in point estimates. We observed that point estimates in most subgroups were substantially similar with the two methods of adjustment. In simulations, the effect estimates differed by a median of 3.4% (interquartile [IQ] range 1.3% to 10.0%). The IQ range exceeded 10% only in cases where the subgroup had <1000 patients or few outcome events. Our empirical and simulation results indicated that using a cohort PS in subgroup analyses was a feasible approach, particularly in larger subgroups.